The Role of Socioeconomic Status, Family Resilience, and Social Support in Predicting Psychological Resilience Among Chinese Maintenance Hemodialysis Patients - Qiu, Yuan; Huang, Yingying; Wang, Yuxin; Ren, Liya; Jiang, Hao; Zhang, Liping; Dong, Chaoqun (Frontiers in Psychiatry, 2021)
Objectives: Evidence on the possible influence of social factors on psychological resilience among maintenance hemodialysis patients is scarce. The aim of this study is to explore the relationship among socioeconomic status, family resilience and social support and psychological resilience among Chinese maintenance hemodialysis patients. Methods: The cross-sectional study was conducted in the hemodialysis center of three comprehensive hospitals in China from September to December 2020 by convenience sampling. Two hundred and fifty-eight patients receiving maintenance hemodialysis were investigated using the sociodemographic questionnaire, Chinese version of the Medical Outcomes Study-Social Support Survey (MOS-SSS), Chinese Family Resilience Assessment Scale (C-FRAS), and Chinese version of the Conner and Davidson resilience scale (CD-RISC). Results: Maintenance hemodialysis patients reported a low level of physical resilience, with a score of (58.92±15.27). Hierarchical linear regression analysis showed that education level (β=.127, p=.018), family’s maintaining a positive outlook (β=.269, p=.001) and positive social interaction support (β=.233, p=.002) and tangible support (β=-.135, p=.037) were significantly associated with psychological resilience. Conclusion: SES, family resilience and social support may be potential predictive factors of psychological resilience. Interventions to improve the family resilience and social supports may be beneficial to promote the psychological resilience of Chinese maintenance hemodialysis patients.